Childhood Maltreatment in Individuals With Schizophrenia Spectrum Disorders: The Impact of Cut-Off Scores on Prevalence Rates - Weitkämper, Angelina; Kellner, Michael; Iffland, Jona Ruben; Driessen, Martin; Kley, Hanna; Neuner, Frank; Iffland, Benjamin (Frontiers in Psychiatry, 2021)
Childhood maltreatment is a common phenomenon in various psychiatric disorders. Accordingly, patients with disorders from the schizophrenia spectrum (SSD) appear to have high prevalence rates of childhood maltreatment. However, the interpretation and comparability of prevalence rates is impeded by methodological weaknesses and differences such as measures and thresholds used in previous studies. Therefore, we aimed to provide and compare systematically captured data on prevalence rates of all common types of childhood maltreatment in patients with SSD using the standardized and well-established Childhood Trauma Questionnaire (CTQ; Wingenfeld et al., 2010) and the most frequently used thresholds following the guidance of Bernstein and Fink (1998) and Walker et al. (1999). The sample consisted of forty-eight patients with a primary diagnosis of SSD. 58.3% to 77.1% of the sample experienced at least one type of childhood maltreatment. Using thresholds reported by Bernstein and Fink (1998), physical neglect (46%) and emotional abuse (44%) were most commonly reported, followed by emotional neglect (38%), physical abuse (25%), and sexual abuse (25%). In comparison, when using cut-off scores according to Walker et al. (1999), higher rates were found for physical neglect (67%), emotional abuse (48%) and physical abuse (38%) while equal rates were found for emotional neglect (38%) and sexual abuse (25%). Additionally, high levels of peer victimization were reported by SSD patients. It appears that Childhood maltreatment is a common phenomenon in SSD, even though methodological details, especially cut-off scores, have a substantial impact on the prevalence rates that are determined. Therefore, the methodology of studies should be closely examined when drawing conclusions from presented prevalence rates.